Fluid Injection and the Mechanics of Frictional Stability of Shale‐Bearing Faults. Issue 10 (8th October 2018) - Scuderi, Marco M.; Collettini, C.
Abstract: Fluid overpressure is one of the primary mechanisms for triggering tectonic fault slip and human‐induced seismicity. This mechanism is appealing because fluid overpressure reduces the effective normal stress, hence favoring fault reactivation. However, upon fault reactivation models of earthquake nucleation suggest that increased fluid pressure should favor stable sliding rather than dynamic failure. Here we describe laboratory experiments on shale fault gouge, conducted in the double direct shear configuration in a true‐triaxial machine. To characterize frictional stability and hydrological properties we performed three types of experiments: (1) stable sliding shear experiments to determine the material failure envelope and permeability, (2) velocity step experiments to determine the rate‐and‐state frictional properties, and (3) creep experiments to study fault slip evolution with increasing pore fluid pressure. The shale gouge shows low frictional strength, μ = 0.28, and permeability, k 10 −19 m 2 together with a velocity strengthening behavior indicative of aseismic slip. During fault pressurization, we document that upon failure slip velocity remains slow (i.e., v 200 μm/s), not approaching dynamic slip rates. We relate this fault slip behavior to the interplay between the fault weakening induced by fluid pressurization, the strong rate‐strengthening behavior of shales, and the evolution of fault zone structure. Our data show that fault rheology and fault stability is controlled by the coupling between fluid pressure and rate‐and‐state friction parameters. Key Points: Laboratory experiments on shale fault gouge designed to test fault slip behavior during fluid pressurization Shale fault gouge fails by accelerated but slow shear slip not evolving into a dynamic slip instability Slow shear slip arises from the interplay of fault hydromechanical properties and fault structure evolution